J Antivir Antiretrovir 2019
DOI: 10.35248/1948-5964.19.11.184
|View full text |Cite
|
Sign up to set email alerts
|

The Botanical Glycoside Oleandrin Inhibits Human T-cell Leukemia Virus Type-1 Infectivity and Env-Dependent Virological Synapse Formation

Abstract: At present, there are no antiretroviral drugs that inhibit incorporation of the envelope glycoprotein into newly-synthesized virus particles. The botanical glycoside, oleandrin, derived from extracts of Nerium oleander, has previously been shown to reduce the levels of the gp120 envelope glycoprotein on human immunodeficiency virus type-1 (HIV-1) particles and inhibit HIV-1 infectivity in vitro. We therefore tested whether oleandrin or an extract from N. oleander could also inhibit the infectivity of the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 84 publications
0
28
0
Order By: Relevance
“…We also reported that oleandrin treatment of cells infected with HTLV-1 resulted in reduced infectivity of progeny virus particles. Oleandrin inhibited virological synapse formation and consequent transmission of HTLV-1 in vitro (18). Collectively this research strongly suggested that oleandrin and defined plant extracts with this molecule have a strong potential against enveloped viruses.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…We also reported that oleandrin treatment of cells infected with HTLV-1 resulted in reduced infectivity of progeny virus particles. Oleandrin inhibited virological synapse formation and consequent transmission of HTLV-1 in vitro (18). Collectively this research strongly suggested that oleandrin and defined plant extracts with this molecule have a strong potential against enveloped viruses.…”
Section: Introductionmentioning
confidence: 60%
“…A recent review described antiviral activities of cardiac glycosides against cytomegalovirus, Herpes simplex virus, adenovirus, chikungunya virus, coronaviruses, respiratory syncytial virus, Ebola virus, influenza virus and human immunodeficiency virus (16). We recently reported that oleandrin, a unique lipid-soluble cardiac glycoside obtained solely from Nerium oleander, has strong antiviral activity against HIV-1 and HTLV-1 (17,18). Importantly, in studies with HIV-1, a unique antiviral activity of oleandrin was observed in terms of producing viral progeny with a greatly diminished potential to infect new target cells (17).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being a cardiac glycoside, oleandrin has been gathering attention due to its anti-tumoral [ 12 , 13 , 14 , 15 , 16 ] and antiviral potential [ 8 , 17 , 18 , 19 ], but its pharmacological use is held back by its variable toxicity. In this study, using the model S. cerevisiae , we detected oleandrin-induced fluctuations in cell Ca 2+ , which could be related to the Ca 2+ entry via the Cch1/Mid1 plasma membrane channel ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…These data further confirmed the Anti-HTLV-1 p19-Gag ELISA results from previous co-culture experiments and demonstrated that oleandrin and the N. oleander phytoextract inhibited HTLV-1 infectivity and Env-dependent VSformation. 19 As others have reported that oleandrin can readily cross the blood-brain barrier and penetrate the CNS in mouse xenograft models of malignant glioma and exhibited neuroprotective effects in vivo models of ischemic stroke,- 7,57,58 this molecule could potentially be used to inhibit HTLV-1 replication and viral gene expression in the CNS and may have therapeutic implications for the treatment of…”
Section: Htlv-1mentioning
confidence: 97%
“…Because of the recent SARS-CoV-2 (COVID-19) worldwide pandemic, attention has been drawn to the antiviral effects of cardiac glycosides and oleandrin as extracts containing this molecule may represent 're-purposing' of a novel molecule. Published reports from in vitro cell culture studies have shown that oleandrin and extracts containing this molecule are effective against HIV, Ebola virus as well as the HTLV-1 and other viruses important to human health and wellbeing; [16][17][18][19] however, it is the unique antiviral mechanisms of oleandrin that merits additional attention. The ability of oleandrin to inhibit the relative infectivity of progeny virus particles may offer a unique approach to treating certain viral diseases.…”
Section: Introductionmentioning
confidence: 99%